THE ROLE OF INVESTMENT PROJECTS IN THE DEVELOPMENT OF THE ECONOMY OF UZBEKISTAN - Mamatov Bahadir Safaraliyevich; Ganiev Shakhriddin Vakhidovich (American Journals, 2024)
The article reveals the essence, content and features of investment projects. The main elements and classification features of investment projects by content, objectives, scale, implementation time, industry focus and proposed financing scheme are analyzed. Based on the conducted research, scientific conclusions were formulated and recommendations for the effective implementation of investment projects in Uzbekistan were developed.
Keywords: Investments, investment project, foreign investments, foreign direct investments, investment environment, flow of foreign investments, public-private partnerships, real investments, priority sectors, financing, fixed capital.